2017
DOI: 10.2224/sbp.6055
|View full text |Cite
|
Sign up to set email alerts
|

Linking Psychological Capital and Feedback-seeking Behavior: Feedback Cognition as a Mediator

Abstract: Although previous researchers have examined the effects of the 4 positive psychological resources of psychological capital (PsyCap) on feedback-seeking behavior, and the influence of PsyCap on proactive behavior, the relationship between PsyCap and feedback-seeking behavior and its underlying mechanism has not been established. Thus, we explored whether or not the link between PsyCap and feedback-seeking behavior was mediated by feedback cognition, by conducting a 3-wave survey with 215 students from 4 univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…As hotel employees face the difficulty of attaching and meeting the requests of guests, they should attend training programs designed by hotel enterprises to develop their competences, knowledge, skills, and abilities. In this regard, their self-efficacy will increase, and this increased self-efficacy will instil confidence in employees in their abilities to overcome difficulties and negative conditions, achieve goals, and maintain a positive state of mind (Wang, Mei, & Zhu, 2017) and will finally result in better performance. What is more, as the successful experiences of employees increase their self-efficacy (Bandura, 1997), it may be suggested to divide difficult and complex tasks into smaller pieces in order to increase the experience of managers and employees and then to teach them one by one (Luthans, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As hotel employees face the difficulty of attaching and meeting the requests of guests, they should attend training programs designed by hotel enterprises to develop their competences, knowledge, skills, and abilities. In this regard, their self-efficacy will increase, and this increased self-efficacy will instil confidence in employees in their abilities to overcome difficulties and negative conditions, achieve goals, and maintain a positive state of mind (Wang, Mei, & Zhu, 2017) and will finally result in better performance. What is more, as the successful experiences of employees increase their self-efficacy (Bandura, 1997), it may be suggested to divide difficult and complex tasks into smaller pieces in order to increase the experience of managers and employees and then to teach them one by one (Luthans, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Lei et al (2020) showed that PsyCap mediates the relationship between transformational leadership and followers' innovation capabilities. PsyCap increases the perceived value of feedback-seeking behavior and encourages people to seek information actively for personal development (Wang et al, 2017). Self-efficacy evokes voice behavior without fear of breaking the status quo (Eibl et al, 2020), helps people face potential risks such as taking action or raising self-expectations, and makes them more willing to take charge of behaviors (Rouzi & Wang, 2021).…”
Section: The Sequential Mediating Role Of Psycap and Job Satisfactionmentioning
confidence: 99%
“…Pode-se observar que vários conceitos e construtos associam de alguma forma a Proatividade e o PsyCap. Um aspecto muito mencionado nos estudos desses conceitos foi o feedback, considerado na literatura essencial para o desenvolvimento do PsyCap (Leroy et al, 2015;Runhaar et al, 2010;Wang et al, 2017). De modo idêntico, pessoas proativas utilizam ativamente o feedback para manter e obter recursos, assim como alcançar objetivos pessoais e profissionais (Li et al, 2010).…”
Section: Construtos E Conceitos Que Aparecem Na Literatura Associados...unclassified
“…Exemplos disso, estão nos estudos de Chen ( 2013), e Klemme Larson e Bell (2013), que concluíram que um construto pode dar origem ao outro, ou seja, o PsyCap pode despertar as práticas proativas, e estas, proporcionarem níveis elevados de PsyCap (Hwang et al, 2015;Xie et al, 2014). Observam-se, ainda, associações e tendências de que o PsyCap e a Proatividade podem se relacionar com outros construtos como o feddback (Leroy et al, 2015;Wang et al, 2017) e o engajamento (Alessandri et al, 2018), que impactam no sucesso da carreira profissional (Cenciotti et al, 2016;Dahling & Whitaker, 2016;Huang, 2017;Pieterse et al, 2010). Enquanto possibilidade de aprender, desenvolver e gerir o PsyCap (Luthans et al, 2007), estudos apontam que outros construtos e conceitos podem ser estudados para compô-lo.…”
Section: Introductionunclassified